Politique de gestion et dégradation persistante des aires naturelles protégées en Côte d’Ivoire : cas de la forêt classée de l’Anguédédou. - Vincent Kouman Mouroufie Kouassi; Oleh Kam; Thierry Ouattara Kouadio Kra (VertigO)
Our article analyzes the way in which the deficiencies in the management of the protected natural area of the Anguédédou sacred forest in Côte d'Ivoire impact its degradation. This study is based on a qualitative approach that led to the interview of twenty-five (36) people, selected according to the principle of purposive data sampling. The results of the study reveal, first, that the actors involved in the management of the Anguédédou Forest have divergent interests. Second, the study shows that socio-economic representations of the forest determine the attitudes and behaviours of the populations, including their social and symbolic practices with respect to the forest. Finally, this study highlights the incoherence of the coordination of the actors' strategies, which reflects the weak synergy of actions of the stakeholders involved in the management of the natural protected area. These results are considered here as explanatory factors for the persistent degradation of the Anguédédou classified forest. This study thus raises questions about the environmental governance of forest resources in the Anguédou forest, but also in other natural protected areas in Côte d'Ivoire.